Accuracy of evidence-based criteria for identifying an incident hip fracture in the absence of the date of injury: a retrospective database study. Issue 7 (17th July 2013) - Vu, Trang; Davie, Gabrielle; Barson, David; Day, Lesley; Finch, Caroline F
Abstract : Objectives: Hospital discharge data (HDD) in many health systems do not capture the date of injury (DOI); the absence of this date hinders researchers' ability to distinguish repeat from incident injury admissions. Various approaches using somewhat arbitrary criteria have been explored to increase the accuracy of incident injury identification. However, these approaches have not been validated against a data source which contains DOI. The aim of this study was to determine the accuracy of evidence-based criteria for identifying fall-related incident hip fractures in the absence of DOI using HDD containing DOI as the reference standard. Design: Retrospective database study. Setting: New Zealand. Participants: 8761 patients aged 65+ years admitted for fall-related hip fracture between 1 July 2005 and 30 June 2008, inclusive. Outcome measures: We defined person-identifying HDD containing DOI as the reference standard and calculated measures of the accuracy of evidence-based criteria for identifying fall-related incident hip fractures from HDD not containing DOI. The criteria were principal diagnosis of hip fracture, mechanism of injury indicating a fall, admission type emergency, admission source other than a transfer and presence of hip operation code(s). For a subsequent fall-related hip fracture, additional criteria were time between successive hip fractures ≥120 days, and all external cause-of-injury codes being different to those for the previous hip fracture. Results: The sensitivity and specificity of the criteria for identifying fall-related incident hip fractures from data not containing DOI were 96.7% and 99.3%, respectively, compared with the reference standard. The application of these criteria resulted in a slight underestimation of the percentage of patients with multiple hip fractures. Conclusions: Although it is preferable to have DOI; this study demonstrates that evidence-based criteria can be used to reliably identify fall-related incident hip fractures from the person-identifying HDD when DOI is unavailable.